The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/oncsis.2017.56
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proton versus photon irradiation on (lymph)angiogenic, inflammatory, proliferative and anti-tumor immune responses in head and neck squamous cell carcinoma

Abstract: The proximity of organs at risk makes the treatment of head and neck squamous cell carcinoma (HNSCC) challenging by standard radiotherapy. The higher precision in tumor targeting of proton (P) therapy could promote it as the treatment of choice for HNSCC. Besides the physical advantage in dose deposition, few is known about the biological impact of P versus photons (X) in this setting. To investigate the comparative biological effects of P versus X radiation in HNSCC cells, we assessed the relative biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 46 publications
5
49
0
Order By: Relevance
“…Bulky tumors (prevailed in our cohort) or CTV>50 cm3 are shown to be associated with higher toxicity and poor outcomes [11,23]. Though, the lower toxicity rate of protons is usually being accounted for in its dose distribution, recent experimental studies reported lower expression of factors involved in lymph-and angiogenesis, in ammation, and immune tolerance [27].…”
Section: Discussionmentioning
confidence: 68%
“…Bulky tumors (prevailed in our cohort) or CTV>50 cm3 are shown to be associated with higher toxicity and poor outcomes [11,23]. Though, the lower toxicity rate of protons is usually being accounted for in its dose distribution, recent experimental studies reported lower expression of factors involved in lymph-and angiogenesis, in ammation, and immune tolerance [27].…”
Section: Discussionmentioning
confidence: 68%
“…Lupu‐Plesu et al . recently published results of an in vitro study in head and neck squamous cell carcinoma cells examining the biological effects of proton versus photon RT for genes involved in anti‐tumor autoimmunity, namely PD‐L1, and found that both proton and photon RT augment PD‐L1 mRNA expression in a dose‐dependent manner . Given our limited cohort size, this question should be addressed in future larger studies since no conclusion can be drawn at this time.…”
Section: Discussionmentioning
confidence: 95%
“…Further work is needed to implement proton therapy in combination with anti‐angiogenic or anti‐immune checkpoint drugs. It is not clear whether the theoretical benefits of proton beam therapy could be translated into clinically meaningful improvement for prostate cancer patients, so any progress implies an urgent need for prospective randomized clinical trials to measure the toxicity and disease control …”
Section: Rebuttalmentioning
confidence: 99%